Suspected child sexual abuse and the role of the health care professional in diagnosis and treatment 2 - Finkel, Martin A. (Henry Stewart Talks, 2018)
Process of medical examination of potential sexual abuse victims, Inappropriate sexual experiences that children can have: common case scenarios, Consequences and treatment of the child sexual abuse